Cooperative Spirit in the XXI Century European Cooperative Culture - Constantinescu, Liliana-Aurora (Procedia economics and finance, 2015)
In this article we want to present the defining features of credit cooperatives as an essential component of economic and social reality of the modern world. A characteristic phenomenon of civilization, a significant component of economic and social activity that carried the interest of a growing number of countries around the world is cooperatives and credit cooperatives in particular. The cooperative is now seen worldwide as a dynamic field of economic and social activity. The beginnings of cooperative activities were promoted by the idea of creating a united organization to improve the economic conditions of the members, getting through mutual economic benefits to be shared equitably. The same ideological principles are valid today only methods to achieve these goals have changed and must continue to change to take part in social, economic and technological.